THE INFLUENCE OF CAMPUS RELIGIOUS CULTURE AND LEGAL POLICIES ON STUDENT RESILIENCE: THE ROLE OF CULTURAL EMPATHY AND EMOTIONAL INTELLIGENCE MEDIATION - Alam, Aztri Fithrayani; Bakhtiar, Muhammad Ilham; Elvera, Resi Sepsilia; Rahman, Khalid; Rustamovich, Ehsonov Jasurbek (Al-Qalam, 2025)
The research aims to analyze the influence of Campus Legal Policy and Campus Religious Culture on Student Resilience, with mediation by using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS 4 application. The researchers collected data from 542 students enrolled in various academic programs and utilized validated instruments to measure campus legal policy, campus religious culture, cultural empathy, emotional intelligence, and student resilience. The key findings are as follows: (1) Campus Religious Culture significantly influences Cultural Empathy, Emotional Intelligence, and Student Resilience; (2) Cultural Empathy significantly influences Emotional Intelligence and Student Resilience; (3) Emotional Intelligence positively influences Student Resilience; and (4) Campus Legal Policy significantly impacts Student Resilience, indirectly affecting it through the mediation of Emotional Intelligence and Cultural Empathy. This research highlights the importance of strengthening campus religious culture and promoting students' affective development through empathy and emotional intelligence, thereby enhancing their academic resilience. These findings have practical implications for campus policies that aim to foster character development and psychological well-being.